History and Development of Islamic Education During the Period of the Prophet Muhammad - Ratu Suntiah; Irfan Ahmad Zain; Hamdan Maulana; Hofifah Astuti (al-Afkar, Journal For Islamic Studies, 2026)
This article discusses how Islamic education changed from the beginning, that is, from the time of the Prophet Muhammad. In the period of the Prophet Muhammad, Islamic education started in a simple way and focused on its inhabitants. In the world of Islamic education, the Prophet Muhammad was the first and foremost teacher. The Prophet Muhammad saw as uswatun hasanah and rahmatan lil'alamin for those who expect grace in the world of Islamic education. The process of change of spiritualism internalization of values and emotional guidance of the Prophet is an extraordinary miracle that cannot be achieved by ordinary people. Islamic education taught at the time of the Prophet was carried out in two stages. Education began in Mecca, which was the initial stage, and education in Medina, which was the second stage of education as an improvement in the guidance of Islamic education. The educational methods used include direct teaching, discussion, and exemplary examples. The results showed that Islamic education in the period of the Prophet succeeded in forming the first generation of Muslims who were noble and knowledgeable.